2018
DOI: 10.1016/j.ymgmr.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year-long enzyme replacement therapy shows a poor effect in alleviating giant leg ulcers in a male with Fabry disease

Abstract: Fabry disease is an X-linked lysosomal storage disorder caused by a deficiency of α-galactosidase A (α-gal A), leading to the progressive accumulation of glycosphingolipids. Classical hemizygous males usually present symptoms, including pain and paresthesia in the extremities, angiokeratoma, hypo- or anhidrosis, abdominal pain, cornea verticillata, early stroke, tinnitus, and/or hearing loss, during early childhood or adolescence. Moreover, proteinuria, renal impairment, and cardiac hypertrophy can appear with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The level of α-gal A activity was measured as previously reported [28]. In short, lymphocytes and skin fibroblasts (SFs) were sonicated, and the whole cell lysates were incubated with a mixture containing 700 mM 4-methylumbelliferyl-α- d -galactopyranoside (4 MUGal; Sigma), 0.5 M N -acetyl- d -galactosamine (GalNAc; Sigma), and 50 mM citrate-phosphate (pH 4.5) buffer in a water bath at 37 °C for 3 h. The reactions were stopped with 150 mM ethylenediaminetetraacetic acid (pH 11.5) buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of α-gal A activity was measured as previously reported [28]. In short, lymphocytes and skin fibroblasts (SFs) were sonicated, and the whole cell lysates were incubated with a mixture containing 700 mM 4-methylumbelliferyl-α- d -galactopyranoside (4 MUGal; Sigma), 0.5 M N -acetyl- d -galactosamine (GalNAc; Sigma), and 50 mM citrate-phosphate (pH 4.5) buffer in a water bath at 37 °C for 3 h. The reactions were stopped with 150 mM ethylenediaminetetraacetic acid (pH 11.5) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of lyso-Gb3 was performed as described before [28]. In short, 60 μL fresh plasma was separated from whole blood and placed into a 1.5 mL tube containing 540 μL 2-propanol (HPLC-grade, Kanto, Japan) and 20 μL internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, only two case studies have mentioned varicose veins in Fabry disease. One of the cases presented bilateral leg ulcers at an early age where venography revealed venous reflux and varicose veins, and further exploration of the family history led to the diagnosis of Fabry disease [28]. The other case report merely noted the presence of lower extremity varicose veins [29].…”
Section: Discussionmentioning
confidence: 97%
“…It is not clear which pathogenetic mechanisms play roles in the development of these ulcers. Okada et al reported a patient with multiple leg ulcers that were refractory to enzyme replacement therapy, and they were able to show venous reflux and varices on the leg venography of their patient. They identified lysosomal deposition of glycosphingolipid as a zebra body in vascular smooth muscle cells and a few accumulations in the vascular endothelium on electron micrograph of the venous biopsy.…”
mentioning
confidence: 97%